Corporate plasticity : how to Change, adapt, and excel - Chevreux, Laurent (Apress business., 2014)
This book demonstrates how plasticity--the ability to change, adapt, and excel as the situation requires--enables organizations to break down barriers and collaborate in the pursuit of a common objective, and to reconfigure or rewire themselves to face down challenges or reach ever-stronger competitive positions. Through entertaining stories and astute analysis, it discusses how plasticity's principles--adaptability, flexibility, fluid networks and roles, lofty goals, and innovation, among others--and the set of abilities for plasticity called the Magic 7--purpose, focus, culture, spirit, networking, knowledge and leadership--are used: to achieve operational excellence; to eliminate wasteful efforts, groupthink, and a reliance on cash cows for revenue and profit; to create more vibrant and creative enterprises; to power up innovative thinking and products; and to respond faster and better to market signals. --